Representações de mulheres sobre violência contra a mulher e qualidade de vida - Amanda Rodrigues Garcia Palhoni (2011)
The present study aimed at understanding womens social representations ofviolence against women and quality of life as well as correlating them. MoscovicisSocial Representation Theory and Jean Claude Abrics Central Nucleus Theory wereused as theoretical and methodological reference. Data was gathered in two steps. Inthe first step, social representations about inductive terms such violence againstwomen and quality of life were apprehended through the free evocation technique.In the second one, the representations found in the first step were clarified andcomplemented through a workshop. The sample was built by 100 women in the firststep and two women in the second step in the same Health Center in the town ofNova Lima, Minas Gerais. These womens profiles description were analyzed throughsimple frequency; the structures obtained through free evocation were processed bythe Ensemble de Programmes Permettant IAnalyses des Evocations (EVOC)software and analyzed under the four-house board technique created by PierreVergès; the hyerarchization orders explanations attributed by the interviewees to theevoked words relating to the induction term and the workshops were evaluated underBardins content analysis. In the womens profiles composition, most of them werebetween 30 and 39 years of age, married with children. Violence against women isrepresented from the disrespect element, such as that which precedes violence andfrom aggression, the most visible expression of violence. The possible causes for itsoccurrence, feelings generated because of it and how it unfolds in the day-by-day lifecomplete this representation. The quality of life representation is built by subjectiveelements such as love, health and work. It happens with elements that should bepresent in peoples lives being explained by the consequences of their absence inones life. The workshop outlined the results found in the studys first step and alsodeepened them through the womens everyday experiences. It can be verified thatthere is a relation between the representation of violence against women and qualityof life in that the quality of life elements aim at fulfill the needs which generateviolence. Under this perspective, it is necessary to think about ways of promotingquality of life also as a strategy of facing violence against women.